PENGARUH BAHAN ORGANIK DAN PUPUK KALIUM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN MELON (Cucumis melo L.) - Safuan, La Ode; Bahrun, Andi (Jurnal Agroteknos, 2012)
The  aim of the research was study the effect of organic matter and potassium fertilizer on   growth   and   production  of   melon.   This   research   was   conducted   in   Rahandouna Subdistrict, Poasia District, Southeast Sulawesi Province, from December 2009 until March 2010. This research was arranged on Split Plot Design, consisting of four levels of organic matter (B) as the main plot : without organic matter (B0),   5 ton.ha-1(B1), 10 ton.ha-1(B2), and  15  ton.ha -1(B3),  and    potassium fertilizer  as  the  sub  plot  consisting of  five  levels: without potassium fertilizer (K0), 50 kg K2O.ha-1 (K1), 100 kg K2O.ha-1 (K2), 150 kg K2O.ha-1 (K3), and 200 kg K2O.ha-1  (K4). Research variables consisted of growth components (stem length, stem circumference, leaf number, and leaf area), production components (fruit weight, fruit circumference, fruit thickness). The result of the  research showed that the interaction of organic matter and potassium fertilizer had no effect on all observed parameters. The aplication of organic matter 10-15 ton.ha-1 and potassium fertilizer 50-150 kg K20 increased growth  and production of melon. The optimum dose of organic matter was 12,25 ton.ha-1 and potassium fertilizer at 150 kg K2O ha.-1 for fresh fruit production, and fruit weight production were 50,40 ton.ha-1  and 54,60 ton ha.-1, respectively. Keywords : fertilizer, growth, potassium, production, organic matter.